Debtor-in-possession financing in reorganization procedures: Regulatory models and proposals for reform - Aurelio GURREA-MARTINEZ (Institutional Knowledge at Singapore Management University, 2023)
A situation of insolvency hinders a firm’s ability to obtain external finance. As a result, viable but financially distressed firms might be unable to keep operating and pursuing value-creating investment projects. Consequently, value can be destroyed for debtors, creditors, employees, suppliers and society as a whole. To address this problem, several jurisdictions around the world have adopted a system of rescue or debtor-in-possession (‘DIP’) financing that seeks to encourage lenders to extend credit to viable but financially distressed firms. They do so by providing DIP lenders with different forms of priority that typically range from a basic administrative expense priority to the possibility of becoming a junior or, in some jurisdictions, even a senior secured creditor. After analysing the regulatory framework of DIP financing in more than 30 jurisdictions in Asia, Latin America, Europe, Africa and North America, this article shows that there are many similarities in the regulation of DIP financing around the world. Yet, there are also significant divergences, especially when it comes to the type of priority that DIP lenders can obtain as well as the system for the approval of DIP financing. The article concludes by examining the risks and costs potentially created by a DIP financing regime. It also discusses whether, and if so how, countries should adopt DIP financing provisions taking into account their legal, economic and institutional environment.